Користь від занять сноубордингом та позитивний вплив на здоров’я людини - Дайнеко Павло; Daineko Pavlo (Видавництво «Код», 2025)
Резюме. Стаття присвячена темі дослідження впливу на здоров’я людини сноубордингу, − нетрадиційного для нашої країни виду спорту, що з кожним роком набуває всі більшої популярності і стає доступним масовим явищем. Тому вивчення впливу від занять сноубордингом набуває все більшої актуальності. На даний момент ми не маємо достатньої кількості літератури та досліджень стосовно сноубордингу у вітчизняному контексті.

Abstract. The article is dedicated to the topic of studying the impact of snowboarding, a non-traditional sport for our country, on human health. Every year this sport is becoming more and more popular and even becomes an accessible mass phenomenon. Therefore, studying the impact of snowboarding is becoming more and more relevant. At the moment, we do not have a sufficient amount of literature and research on snowboarding in the domestic context. For this reason, this article collects characteristics and conclusions of foreign experience, since we simply do not have such coverage of the topic of the benefits of snowboarding in our information space. Of particular note is a completely new sub-sport for our country, namely adaptive snowboarding, which is starting to develop quite successfully. In addition to the adrenaline rush and picturesque mountain landscapes, snowboarding actually has many health benefits, which makes it much more than just a seasonal pastime. The health benefits of snowboarding on people are extremely important – from physical exertion to mental well-being. Whether you are an experienced athlete or just starting to explore the slopes, snowboarding is a great full-body workout that will help you stay fit and healthy all year round. In this article, we looked at the numerous health benefits of snowboarding and found out why it is more than just a winter sport. The combination of cardio and muscle training helps build muscle mass, increasing metabolic rate and contributing to long-term weight control. Unlike monotonous workouts, snowboarding maintains physical activity and motivation, makes it easier to maintain a constant exercise regimen, creates a variety of challenges that require quick thinking and adaptability; promotes a sense of achievement and confidence in mastering new skills and overcoming difficulties in the mountains. This winter sport is a great way to unwind and relax. Snowboarding allows you to forget about everyday problems and relieve emotional tension, which has a beneficial effect on a person’s psychological state.The results and recommendations obtained can serve as the basis for further research in the direction of snowboarding development in Ukraine, optimization of educational sports programs and their adaptation to the challenges of the modern world.
Benefits of snowboarding and positive impact on human health
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: спорт; сноубординг; тренування; користь; вплив